2020
DOI: 10.3390/cancers12113463
|View full text |Cite
|
Sign up to set email alerts
|

DNAJA3/Tid1 Is Required for Mitochondrial DNA Maintenance and Regulates Migration and Invasion of Human Gastric Cancer Cells

Abstract: Background: Gastric cancer is a common health issue. Deregulated cellular energetics is regarded as a cancer hallmark and mitochondrial dysfunction might contribute to cancer progression. Tid1, a mitochondrial co-chaperone, may play a role as a tumor suppressor in various cancers, but the role of Tid1 in gastric cancers remains under investigated. Methods: The clinical TCGA online database and immunohistochemical staining for Tid1 expression in tumor samples of gastric cancer patients were analyzed. Tid1 knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 80 publications
4
46
0
Order By: Relevance
“…Tid1 maintains and regulates the normal mitochondrial function and ROS homeostasis [ 21 , 24 ]. During tumorigenesis, downregulation of Tid1 can cause abnormal ROS, which can be counteracted by the antioxidant transcriptional factor, Nrf2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tid1 maintains and regulates the normal mitochondrial function and ROS homeostasis [ 21 , 24 ]. During tumorigenesis, downregulation of Tid1 can cause abnormal ROS, which can be counteracted by the antioxidant transcriptional factor, Nrf2.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we reported that the HNSCC patients with higher expression of Tid1 have better overall survival [ 19 , 20 ]. Most recently, we also discovered that Tid1 can function as a tumor suppressor in gastric cancer progression [ 21 ]. It has been reported that Tid1 plays an important role to maintain mitochondrial DNA [ 21 ], membrane potential [ 22 ], and cristae structure [ 23 ], and to modulate the intracellular reactive oxygen species (ROS) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been well documented in the case of galectin-7/Bcl-2 interactions [52]. Galectin-7 is also targeted by Tidf1, which represses the oncogenic role of galectin-7 by promoting its degradation [49]. Whether de novo expression of Tidf1 represses galectin-7-induced MMP-9 expression is an interesting possibility that has not, to our knowledge, been studied.…”
Section: How Does Galectin-7 Induce Mmp-9?mentioning
confidence: 91%
“…It was first reported in an experimental lymphoma mouse model, in which the expression of galectin-7 by lymphoma cells was shown to increase the aggressive behavior of lymphoma cells by inducing MMP-9 [27]. We and others have since shown that galectin-7 can induce MMP-9 in breast cancer, ovarian cancer, head and neck cancer, cervical and oral squamous cell carcinomas and, more recently, gastric cancer cells [44][45][46][47][48][49]. In some cases, this association between galectin-7 and MMP-9 was found to be specific, as no such association was found between MMP-9 and galectin-1 or galectin-3 [44,45].…”
Section: De Novo Expression Of Galectin-7 By Mutated P53mentioning
confidence: 99%